Identifying nutrition-sensitive development options in Madagascar through a positive deviance approach - Arielle Sandrine Rafanomezantsoa; Claudia Coral; Narilala Randrianarison; Christoph Kubitza; Denis Randriamampionona; Harilala Andriamaniraka; Stefan Sieber; Sarah Tojo-Mandaharisoa; Jonathan Steinke (Food Security, 2022)
Abstract Context-adapted interventions are needed to alleviate the burden of food and nutrition insecurity on resource-poor rural households in southeastern Madagascar. The Positive Deviance approach implies identifying locally viable development solutions by focusing on particularly successful, innovative individuals. To identify promising practices that could be promoted as part of food and nutrition security (FNS) interventions in the Atsimo Atsinanana region of southeastern Madagascar, positive deviance was searched among smallholder farmers. Positive deviants are defined as households with overall optimal performance across four aspects of FNS: household-level food security, women's diet quality, child's diet quality, and low diarrhea incidence. To identify positive deviants, a two-step procedure was followed. Based on quantitative survey data from 413 rural smallholder households (mother-child pairs) with a child aged between 6 and 23 months, each household's four performance scores were adjusted by removing the average effects of household resources. Then, households with Pareto-optimal performance were identified regarding the four aspects. Subsequently, 16 positive deviants were revisited and positive deviant practices were identified through in-depth interviews. A set of practices were validated through focus group discussions with local nutrition and agriculture experts. Positive deviant practices include the adoption of agricultural innovation, such as new cash crops, as well as nutrition-sensitive market behaviors and reliance on off-farm activities. In addition, some ethno-cultural factors help to explain positive deviance. These diverse positive deviant practices may serve as examples and inspiration for locally grounded development interventions targeting FNS in southeastern Madagascar.
Keywords: 330; Positive deviants; Atsimo Atsinanana; Nutrition; Food security; Madagascar